Hygiene Principles Training for Rural Food SMEs in Kaliagung Village, Kulon Progo, D.I. Yogyakarta - Sari, Anjar Ruspita; Putri Rousan Nabila; Fajar Budi Lestari; Febri Ariyanti; Rochmad Hidayat; Singgih Utomo; Achmad Yoga Sundava; Nara Husnal Aufa (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Small and Medium Enterprises (SMEs) operating within rural communities frequently encounter significant hurdles in the effective implementation of food hygiene and sanitation protocols. This struggle is largely attributable to limited financial resources and a critical deficit in fundamental food safety knowledge. A critical gap exists in the understanding of relevant food safety legislation, which often results in non-compliance with significant implications for regulatory enforcement. In response to this pervasive need, a targeted training intervention was developed and executed for food SME operators in Kaliagung Village. The objective of the training was to empower participants by equipping them with the general principles of food hygiene and sanitation. The training employed an interactive methodology, strategically blending theoretical presentations with practical, site-specific self-assessments. The program was rigorously designed based on the Indonesian National Standard (SNI) CAC/RCP 1:2011, focusing on five critical domains: environmental sanitation, facility hygiene, personal hygiene, process control, and record-keeping. The effectiveness of the program was evaluated using pre- and post-training assessments to quantify changes in participants' knowledge and comprehension. The evaluation demonstrated a positive and substantial impact, with the average participant score on food hygiene knowledge increasing from 3.5 to 4.85 (using 5 scale). This statistically reflected increase in the average score validates the utility of the training activity. In conclusion, this program highlights the critical role of structured training in enhancing food safety practices within rural communities. By providing practical, standards-based knowledge, such interventions are vital for fostering a safer and more compliant food industry landscape in these key areas.